(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
This article analyzes the semantic and morphological characteristics of railway terminology. The study explores the development of railway terms and their usage in international, Russian, and local contexts. It highlights how technological advancements and global integration processes influence the meaning of terms. The role of translation strategies, such as transliteration, adaptation, and equivalent phrasing, is also discussed. The semantic evolution and morphological structure of railway terminology contribute to effective communication in global processes. The findings confirm the dominance of international terms while emphasizing the necessity of developing national terminology systems to align with global standards.